Floods in a changing climate : extreme precipitation - Teegavarapu, Ramesh S. V., 1970- (Cambridge : Cambridge University Press, 2012)
'Measurement, analysis and modeling of extreme precipitation events linked to floods is vital in understanding changing climate impacts and variability. This book provides methods for assessment of the trends in these events and their impacts. It also provides a basis to develop procedures and guidelines for climate-adaptive hydrologic engineering. Academic researchers in the fields of hydrology, climate change, meteorology, environmental policy and risk assessment, and professionals and policy-makers working in hazard mitigation, water resources engineering and climate adaptation will find this an invaluable resource. This volume is the first in a collection of four books on flood disaster management theory and practice within the context of anthropogenic climate change. The others are: Floods in a Changing Climate: Hydrological Modeling by P. P. Mujumdar and D. Nagesh Kumar, Floods in a Changing Climate: Inundation Modeling by Giuliano Di Baldassarre and Floods in a Changing Climate: Risk Management by Slodoban Simonovi{u28E2}--
'Measurement, analysis and modeling of extreme precipitation events linked to floods is vital in understanding the world's changing climate. This book examines and documents the impacts of climate change and climate variability on extreme precipitation events, providing methods for assessment of the trends in these events, and their impacts. It also provides a basis to develop procedures and guidelines for climate-adaptive hydrologic engineering. Topics covered include approaches for assessment of hydrometerological floods, recent developments in hydrologic design for flood mitigation, and applications and limitations of improved precipitation forecasts, using information about internal modes of climate (teleconnections). State-of-the-art methodologies for precipitation analysis, estimation and interpolation are included, and exercises for each chapter, supported by modelling software and computational tools available online at www.cambridge.org/teegavarapu, enable the reader to apply and engage with the innovative methods of assessment'--
Machine generated contents note: Part I. Precipitation Processes and Measurement: 1. Precipitation and climate change; 2. Precipitation measurement; 3. Spatial analysis of precipitation data; Part II. Extreme Precipitation, Floods and Climate Change: 4. Extreme precipitation and floods; 5. Precipitation modeling and climate change; Part III. Precipitation Variability, Teleconnections and Trends: 6. Precipitation variability and teleconnections; 7. Global precipitation trends and variability; Part IV. Hydrologic Modeling and Design in a Changing Climate: 8. Hydrologic modeling and design; 9. Future perspectives; References; Index.
Includes bibliographical references (pages 253-265) and index.
Keywords: Precipitation (Meteorology) -- Measurement; Floods -- Mathematical models; Hydrologic models; Climatic extremes; Climatic changes -- Environmental aspects